Factors associated with sexual intimacy among Malaysian elderly couples: a cross-sectional study - Minhat, Halimatus Sakdiah; Mat Din, Hazwan; Tengku Abdul Hamid, Tengku Aizan; Hassan Nudin, Siti Sa’adiah (Academy of Sciences Malaysia, 2019)
Sexual intimacy is an essential aspect of life regardless of age and proven to increase the quality of life of older persons. This study aimed to identify the determinants that predict sexual intimacy among elderly couples in Malaysia. A total of 1934 elderly were selected throughout Peninsular Malaysia and also Sabah and Sarawak. A validated questionnaire was used consisted of sociodemographic information, presence of chronic diseases, perceived present health status, satisfaction with current life, Body Mass Index, disability, social support and sexual intimacy sections. Despite still sleeping with their spouses (60.8%), majority of the respondents claimed incapable of having sexual intercourse (71.0%). Good sexual intimacy in later life was determined by being married and received good social support from family members and friends. On the other hand, those who aged 70 and above, female, non-Malay, had informal education, had gastritis, perceived their current health status as satisfactory, unsatisfied with current lifestyle and disabled were having a significant likelihood of having poor sexual intimacy at old age. The findings indicated the importance of being healthy and having good social support, which includes still having a spouse to maintain sexual intimacy in old age.